2020
DOI: 10.1039/d0nj01439g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV stability of N-halamine-immobilized Fe3O4@SiO2@TiO2 nanoparticles: synthesis, characteristics and antibacterial property

Abstract: Recycling of N-halamine-modified Fe3O4@SiO2@TiO2 antibacterial materials with UV stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The peak at 786 cm –1 was considered the symmetric stretching vibration of Si–O–Si, and the band with a peak at 945 cm –1 was ascribed to the transverse optical asymmetric stretching vibration of the Si–O–Si bond or/and Si–O–C units, all related to amorphous SiO 2 . 46 48 This result was consistent with the XRD and FTIR results. From the above-mentioned characterizations, it could be suggested that the combination of fast annealing and quenching successfully produced the SiO 2 /C material with a highly porous structure.…”
Section: Resultssupporting
confidence: 90%
“…The peak at 786 cm –1 was considered the symmetric stretching vibration of Si–O–Si, and the band with a peak at 945 cm –1 was ascribed to the transverse optical asymmetric stretching vibration of the Si–O–Si bond or/and Si–O–C units, all related to amorphous SiO 2 . 46 48 This result was consistent with the XRD and FTIR results. From the above-mentioned characterizations, it could be suggested that the combination of fast annealing and quenching successfully produced the SiO 2 /C material with a highly porous structure.…”
Section: Resultssupporting
confidence: 90%
“…13 An early ab initio study 15 showed that the N–Cl bond is rather weak, and a more recent high-level quantum chemical study 16 highlights the effect of substituents on the strength of N–Cl bond dissociation energy. N–Cl bonds in N -halamine-based materials are not stable under UV light irradiation, 17 and a reaction mechanism in which the N–Cl bond is cleaved by UV has been proposed for the transformation reaction of the micropollutant atenolol. 18 To slow down the dissociation of the N–Cl bond in NCLBA, we performed the experiment at a very low temperature of 17.5 K, extracting a high-quality charge density distribution from the high-resolution diffraction pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Fe 3 O 4 particles were prepared using the co-precipitation method [32]. FeCl 3 • 6H 2 O (8.1 g, 30 mmol) and FeCl 2 • 4H 2 O (3.4 g, 17 mmol) were added to a 250 mL round-bottom flask containing 100 mL distilled water.…”
Section: Synthesis Of Magnetic Nanoparticles Fe 3 Omentioning
confidence: 99%